2001
DOI: 10.5380/cep.v19i1.1219
|View full text |Cite
|
Sign up to set email alerts
|

EFEITO DO COZIMENTO CONVENCIONAL SOBRE OS CAROTENÓIDES PRÓ-VITAMÍNICOS "A" DA POLPA DO PIQUI (Caryocar brasiliense Camb)

Abstract: Visou-se caracterizar os carotenóides, avaliar sua atividade próvitamínica “A” e verificar as perdas destes pigmentos decorrentes do cozimento convencional da polpa do piqui (Caryocar brasiliense Camb) com arroz, simulando o preparo de acordo com os hábitos regionais. Tanto as amostras cruas quanto as cozidas apresentaram os mesmos carotenóides: ­caroteno, ­caroteno, criptoflavina, ­criptoxantina, anteraxantina, zeaxantina e mutatoxantina. O valor médio de carotenóides foi de 231,09 e 154,06 g/g de polpa c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
24
3
18

Year Published

2008
2008
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(53 citation statements)
references
References 2 publications
1
24
3
18
Order By: Relevance
“…The results of this study can be correlated with those obtained by Ramos et al (2001), who found that β-carotene is one of the main carotenoid of both raw and cooked pequi pulp (0.93 mg.100 g -1 ) (1.22 mg.100 g -1 ). However, they contradict those of Azevedo-Meleiro and Rodriguez Amaya (2004), who indicate violaxanthin, lutein, and zeaxanthin as the main carotenoids of the pequi pulp demonstrating the need for further research on the identity and amount of the carotenoids present in the oil and pulp of this fruit.…”
Section: Resultssupporting
confidence: 78%
See 2 more Smart Citations
“…The results of this study can be correlated with those obtained by Ramos et al (2001), who found that β-carotene is one of the main carotenoid of both raw and cooked pequi pulp (0.93 mg.100 g -1 ) (1.22 mg.100 g -1 ). However, they contradict those of Azevedo-Meleiro and Rodriguez Amaya (2004), who indicate violaxanthin, lutein, and zeaxanthin as the main carotenoids of the pequi pulp demonstrating the need for further research on the identity and amount of the carotenoids present in the oil and pulp of this fruit.…”
Section: Resultssupporting
confidence: 78%
“…Regardless of the extraction method used, the pequi oil total carotenoids level were higher than those found in the pulp of the fruit in the studies of Lima et al (2007), who found the equivalent to 7.25 mg.100 g -1 of carotenoids, and that of Ramos et al (2001), who found levels of 23.11 and 15.41 mg.100 g -1 of total carotenoids in the raw and cooked pulp, respectively. These carotenoid values demonstrate that the pequi oil, as well as the fruit, is an excellent carotenoid source.…”
Section: Resultsmentioning
confidence: 66%
See 1 more Smart Citation
“…A secagem à temperatura de 60 °C por 16 horas e a secagem ao sol promoveram praticamente a destruição dos carotenoides do óleo de pequi. Estes valores estão próximos ao encontrado por Ramos et al (2001) para a polpa de pequi crua (231,09 µg.g -1 ). De forma semelhante, Ramos (1987) verificou uma maior perda de carotenoides totais no pequi com o aumento da temperatura de secagem.…”
Section: Resultsunclassified
“…Frutos do cerrado e do pantanal têm sido avaliados quanto à composição em nutrientes e carotenóides, visando o conhecimento de matérias-primas regionais (RAMOS et al, 2001;HIANE et al, 2003;CALDEIRA et al, 2004).…”
Section: Introductionunclassified